Pengembangan Sistem Persuratan PT PGAS Solution - Ajeng Ardhia Arya Kusuma Putri; Denny Sagita Rusdianto; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Process of letter managing and dispositioning in PT PGAS Solution is not effective and takes a long time. This condition causing various problems such as wrong recipients of dispositions, the recipient who is not in the office, late implementation, has no report, and often loss disposition sheet that has been distributed. Therefore, a website-based system is established where the required engineering needs a total of 23 functional requirements and 1 non-functional requirement. These needs are designed and implemented through an object-oriented approach, using Ruby on Rails (RoR). RoR was chosen because this framework builds websites by abstracting and simplifying the most repetitive tasks. Rails and most of its libraries are also open sources. In white-box testing carried out through unit testing and integration testing, the value of the cyclomatic complexity calculation obtained from each test case is between 1-10. In the validation test, a test of 35 test cases was carried out with the conclusion that the system can run well. Then in compatibility testing, the system successfully runs on 4 different browsers without any fatal errors. Through this development, a system which can facilitate the management of the letter and its dissociation process is produced.